2014
DOI: 10.1158/1535-7163.mct-13-0634
|View full text |Cite
|
Sign up to set email alerts
|

Nedd8-Activating Enzyme Inhibitor MLN4924 Provides Synergy with Mitomycin C through Interactions with ATR, BRCA1/BRCA2, and Chromatin Dynamics Pathways

Abstract: MLN4924 is an investigational small-molecule inhibitor of the Nedd8-activating enzyme currently in phase I clinical trials. MLN4924 induces DNA damage via rereplication in most cell lines. This distinct mechanism of DNA damage may affect its ability to combine with standard-of-care agents and may affect the clinical development of MLN4924. As such, we studied its interaction with other DNA-damaging agents. Mitomycin C, cisplatin, cytarabine, UV radiation, SN-38, and gemcitabine demonstrated synergy in combinat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 40 publications
2
44
0
Order By: Relevance
“…42). In additional preclinical studies, pevonedistat has demonstrated synergy in combination with azacitidine in AML cell lines and murine xenografts (43) and increased antitumor activity in certain solid tumor cell lines and xenograft models when combined with DNA-damaging agents including cisplatin, carboplatin, mitomycin C, and dacarbazine (17,22,28,44,45). Consequently, the focus of ongoing investigations is of pevonedistat in various combination regimens including with azacitidine in elderly AML patients (NCT01814826; ref.…”
Section: Discussionmentioning
confidence: 99%
“…42). In additional preclinical studies, pevonedistat has demonstrated synergy in combination with azacitidine in AML cell lines and murine xenografts (43) and increased antitumor activity in certain solid tumor cell lines and xenograft models when combined with DNA-damaging agents including cisplatin, carboplatin, mitomycin C, and dacarbazine (17,22,28,44,45). Consequently, the focus of ongoing investigations is of pevonedistat in various combination regimens including with azacitidine in elderly AML patients (NCT01814826; ref.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulation of cell cycle regulatory proteins upon MLN4924 treatment was constantly accompanied with DNA damage response, which was partially responsible for the apoptosis and senescence induced upon NEDDylation inhibition (Soucy et al 2009a, b;Mackintosh et al 2013;Jia et al 2011a, b). Given the potency and the unique mechanism of MLN4924 in inducing DNA damage in cancer cells, synergistic interactions between MLN4924 with other DNA-damage-inducing compounds (platinum, cytarabine, Cisplatin, mitomycin C) and radiation will promote its incorporation into current treatment regimens for human malignancies (Nawrocki et al 2013(Nawrocki et al , 2015Yang et al 2012;Wei et al 2012;Kee et al 2012;Jazaeri et al 2013;Garcia et al 2014). These studies highlighted potential incorporation of MLN4924 into current treatment regimens as addition of MLN4924 was shown to sensitize malignant cells to those traditional therapeutic strategies.…”
Section: Skp2mentioning
confidence: 99%
“…In various experiments, cells were incubated with inhibitors of translation (CHX, at 50 μg/mL) (26), the proteasome (MG132, at 10 μM) (63), lysosome functionality (CQ, at 100 μM) (64), and neddylation (MLN4924, at 1 mM) (47). ES cell cultures were treated with TSA (100 ng/mL) and FSK (10 μM) to release the silencing of the CMV promoter (28,29).…”
Section: Methodsmentioning
confidence: 99%
“…Neddylation of one or more subunits activates the CRL complexes and promotes their protein degradation activities (46). A small-molecule inhibitor, MLN4924, blocks the neddylation activity of Nedd8, which is required for the activation of Cullin proteins (47,48). To test whether neddylation is important for ZFP809 degradation, we examined the half-life of ZFP809 in the presence of MLN4924.…”
Section: Rapid Degradation Of Full-length Zfp809 Protein In Differentmentioning
confidence: 99%